Gearing ratio - Kleshnev, V. (Rowing Biomechanics Newsletter, 2015)
The standard definition of the gearing is the ratio of the velocities at output to input. Higher, heavier gearing, say, in cycling or cars, means higher vehicle velocity at lower engine rotation speed, but lower propulsive force, and vice versa. In this article, the object ist the total gearing in rowing, which could be defined as the ratio of the boat velocity Vboat relative to the water to the rower`s velocity Vrow relative to the boat.